THE ANALYSIS OF COMPLEX LITERARY TERMS IN “THE CONCISE OXFORD DICTIONARY OF LITERATURE TERMS” BY Ch. BALDICK (Scientific journal of the Fergana State University, 2023)
The scientific research shows that literary terms in the Germanic languages were not studied uniformly. Literary terms, which were the subject of our research, have hardly been studied in the Slavic, Roman and Germanic languages. Objectives and methods: Therefore, it is relevant to study the terms of philosophy, culture and spirituality, ethics, aesthetics, religion, linguistics and especially literary criticism. The degree of study and significance of literary terms are carried out in the given article. The article gives classification of complex literary terms of the dictionary “The Concise Oxford Dictionary of Literary Terms” by  Chris Baldick.